Do the candidates matter? A theory of agency in American presidential nominations - Nwokora, Z (2009)
This thesis develops a candidate-centred conception of American presidential nominations. Candidates' choices in nomination politics remain under-theorised. The literature on nominations has tended either to downplay the role of candidates' independent influence or to suggest that the impact of their choices is too idiosyncratic to theorize about. I reject both of these positions; and instead develop the basic elements of a theory in which candidates are the principal agents of change in nomination contests. I argue that candidates make distinct identity, tactical, and management choices, and I show that this simple frame can be used to connect aspirants’ varying goals to their choices and actions. In my theory, candidates' prospects remain relatively stable unless a shift occurs in their competitive setting in response to an unexpected event – for instance, a surprising election result. These shifts, or critical junctures, define a candidate's path to his party’s presidential nomination. I argue that the rival candidates' choices dominate the development of these critical junctures and, therefore, that candidates' choices are crucial to nomination outcomes. Structural factors, the actions of non-candidates and the effects of exogenous events, account for a minority of critical junctures. In the empirical chapters of this study, I examine the Democratic and Republican nomination contests in selected years before the McGovern-Fraser reforms (1912, 1924, 1932) and in post-reform cases (1972, 1976, 1980) to demonstrate the pervasive influence of candidates' choices in contrasting institutional settings. These cases confirm my basic claim about the centrality of candidates' choices and also suggest significant ways in which candidates’ choices have changed between 1912 and 1980.